PENGARUH PENGGUNAAN SERBUK KAYU JATI DAN SIKA VISCOCRETE TERHADAP KUAT TEKAN BETON - febryandi; Sinta Devi, Debby; Marlina, Leni (UNIVERSITAS INDO GLOBAL MANDIRI, 2024)
ABSTRACT Due to the growing infrastructure, the use of concrete construction is increasing. Concrete is a construction material made from a mixture of coarse aggregate, fine aggregate, cement, water, and other additives. Teak wood powder is a sawn residue from wood waste that is utilized as a fine aggregate substitute. Teak wood powder contains cellulose, hemilose, and lignin, and has the ability to bind materials well and inhibit water diffusion so as to increase the compressive strength of concrete. In addition, the addition of Sika viscocrete is also carried out to increase the compressive strength of concrete. This research analyzes the use of teak wood powder as fine aggregate with variations of 5%, 10% and 15% and sika viscocrete 0.8% by weight of cement. The test results obtained at the compressive strength of 28 days of age with the use of 5% teak wood powder is 28.03 MPa, while for 10% variation of 28 days of age obtained compressive strength of 22.04 MPa, for 15% variation of 28 days of concrete compressive strength of 20.76 MPa. The use of teak wood powder at 5% can increase the compressive strength of concrete by 6.3% compared to normal concrete added with Sika viscocrete. In addition, when compared to normal concrete without sika viscocrete, the increase occurred by 9.09%. Therefore teak wood powder can be used as an effective additive to increase the compressive strength of concrete, as well as making a positive contribution to sustainability in the construction industry. Keywords: Teak wood powder, sika viscocrete, concrete compressive strength ABSTRAK Konstruksi beton semakin populer seiring dengan kemajuan infrastruktur. Beton adalah bahan konstruksi yang terbuat dari campuran agregat kasar, agregat halus, semen, air, dan bahan tambahan lainnya. Serbuk kayu jati merupakan sisa pengergajian dari limbah kayu yang dimanfaatkan sebagai substitusi agregat halus. Serbuk kayu jati mengandung selulosa, hemilosa, dan lignin, dan memiliki kemampuan untuk mengikat material dengan baik serta menghambat difusi air sehingga dapat meningkatkan kekuatan tekan beton. Selain itu penambahan sika viscocrete juga dilakukan untuk menambah kuat tekan beton. Pada penelitian ini bertujuan untuk mengetahui bagaimana pengaruh penggunaan serbuk kayu jati sebagai agregat halus dengan variasi 5%,10% dan 15% dan sika viscocrete 0,8% terhadap berat semen. Hasil uji yang didapatkan pada kuat tekan umur 28 hari dengan penggunaan 5% serbuk kayu jati adalah sebesar 28,03 MPa, sedangkan untuk variasi 10% umur 28 hari didapatkan kuat tekan sebesar 22,04 MPa, untuk variasi 15% umur 28 hari kuat tekan beton 20,76 MPa. Penggunaan serbuk kayu jati sebesar 5% dapat meningkatkan kuat tekan beton sebesar 6,3% dibandingkan dengan beton normal ditambah dengan sika viscocrete. Selain itu jika dibandingkan dengan beton normal tanpa sika viscocrete peningkatan terjadi sebesar 9,09%. Oleh karena itu serbuk kayu jati dapat digunakan sebagai bahan tambahan yang efektif untuk meningkatkan kuat tekan beton, serta memberikan kontribusi positif terhadap keberlanjutan dalam industri konstruksi. Kata Kunci: Serbuk kayu jati, sika viscocrete, kuat tekan beton